Hematological changes caused by vaginal delivery - Ayllón B., Guigliana (2015)
In order to investigate the hematologic changes that result after delivery, a prospective study was carried on the pregnants that entered to the Maternity Hospital of Lima at beginning of labor. Distocic deliveries were not considered, remaining a group of 150 patients at random, 56 patients were primiparas and 96 were multiparas. Mean hemoglobin value, before the delivery, was 10.98 gm/100 ml. ± 1.57 prior to delivery: where as 9,95 gm./100 ml. ± 1.59 was found after delivery, 71,3% of the patients had less than 12.0 gm/100 ml. at he beginning of labor, figure that incresed to 88,7% after delivery. The proportion of anemic women pre and post partum classified by material age, parity, pre-natal evaluation and the practice of episiotomy showed differences of statistical significance.